Bringing out the best in people [ how to apply the astonishing power of positive reinforcement - Daniels, Aubrey C. (McGraw-Hill, 2000)
The classic bestseller on performance management is updated to reflect changes in today's working environment. When an employer needs to know how to gain maximum performance from employees, renowned behavioral psychologist--Aubrey Daniels is the man to consult. What has made Daniels the man with the answers? His ability to apply scientifically based behavioral stimuli to the workplace while making it fun at the same time. Now Daniels updates his ground-breaking book with the latest and best motivational methods, perfected at such companies as Xerox, 3M, and Kodak. All-new material shows how to: create effective recognition and rewards systems in line with today's employees want; Stimulate innovations and creativity in new and exciting ways; overcome problems associated with poorly educated workers; motivate young employees from the minute they join the workforce. -- Description from http://www.booktopia.com.